Digital Financial Services : Challenges and Opportunities for Emerging Market Banks - Saal, Matthew; Starnes, Susan; Rehermann, Thomas (International Finance Corporation, Washington, DC, 2018)
A digital transformation is taking place in the financial services industry, with a host of non-bank innovators offering both customer facing and back office financial technology products and services. This transformation includes emerging market economies, and in many places offers a viable digital alternative to traditional banks, which have left significant populations underbanked. This note explores the challenges and opportunities that financial technology innovations present for banks in these nations.